Prevalence of chronic kidney disease in the community in the United Kingdom in OxRen, a population-based cohort study - Hirst, J; Hill, N; O'Callaghan, C; Lasserson, D; McManus, R; Ogburn, E; Ordonez-Mena, J; Shine, B; Taylor, C; Vazquez Montes, M; Yang, Y (Royal College of General Practitioners, 2020)
Background: Chronic kidney disease (CKD) is a largely asymptomatic condition of diminished renal function, which may not be detected until advanced stages without screening.